2011
DOI: 10.1007/s10704-011-9615-9
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Evaluation of Stress-Optical Constants by Caustics

Abstract: A study of the experimental evaluation of the stress-optical constants accurate values was undertaken by the method of caustics. A series of experiments were performed in single edge-cracked specimens made of Plexiglas (PMMA). It was found that the values of the stress-optical constants were varied with the load and the thickness of the specimens. This means that a three-dimensional stress conditions hold in the neighbourhood of the crack tip. The accurate stress intensity factor K I can be experimentally eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…, for plane stress state (13) Fig. (3) illustrates the experimental stress intensity factors (normalized to C) calculated by the diameters D t and D  and shape area, A, of the caustic versus the tensile stress for the same crack length α = 0.040m.…”
Section: Methods Of Reflected Causticsmentioning
confidence: 99%
See 1 more Smart Citation
“…, for plane stress state (13) Fig. (3) illustrates the experimental stress intensity factors (normalized to C) calculated by the diameters D t and D  and shape area, A, of the caustic versus the tensile stress for the same crack length α = 0.040m.…”
Section: Methods Of Reflected Causticsmentioning
confidence: 99%
“…Then, a new formula for the evaluation of the stress intensity factor which was based on the caustic area, was applied [10]. By this formula, a new approach to evaluate the stress optical constants [13]. Recent work [14][15][16] has demonstrated that the method of caustics can be used to study the plasticity around the crack tip.…”
Section: Introductionmentioning
confidence: 99%